An algorithm for fatigue crack growth applied to mixed and biaxial mode loadings - Baptista, Ricardo (2019)
Submitted by Marta Frade (marta.diogo@ess.ips.pt) on 2019-09-16T13:21:42Z No. of bitstreams: 1 1-s2.0-S2452321619302781-main.pdf: 679009 bytes, checksum: 07748e1badcf5af9b45df6847cb481fa (MD5)